Towards effective subject leadership in a rural primary school by developing collaborative teacher learning - Woodward, R (2021)
This research explores the development and improvement of foundation subject leadership within a rural primary school. This study was conducted over a 3-month period and explored how collaborative teacher learning could improve the development of teacher’s leadership. The aim of this research was to help accommodate the improvement of foundation subject leadership in the unique setting. A rural school is typically defined as a school with less than 100 pupils (Cade, Ferguson, Gale, Holt, & Neaum, 2018). The implications of this are that in these settings there are significantly less staff, which in turn increases workload and lowers staff effectiveness. This research explores the use of collaborative learning as a means to help problem solve subject leadership with little staff. This research shows how this approach can have a positive impact; however, it can be viewed that this project is a starting point to help plan for further development of research within this area.